2006
DOI: 10.7224/1537-2073-8.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Living With Multiple Sclerosis in New South Wales, Australia, at the Beginning of the 21st Century: Impact of Mobility Disability

Abstract: This article is the initial report on the Multiple Sclerosis (MS) Society of New South Wales (NSW) Client Census Database study, a telephone-based cohort study of registered clients of the society in 2001. The final database sample comprised 2618 respondents with a diagnosis of MS from the registered client database, representing 73% of this target client population and an estimated 70% of all people with MS in NSW, Australia. The mean age was 49 years, and mean time since diagnosis was 11 years, with 36% diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…A majority of both male and female survey respondents came from the 45-64 age groups. The demographic characteristics of respondents to the 2003 survey were similar to those of other contemporary Australian studies [3,24], supporting the suggestion that respondents were broadly representative of Australians with MS. Some of the differences that were found with published studies are described below (see Discussion: limitations of study).…”
Section: Respondentssupporting
confidence: 71%
“…A majority of both male and female survey respondents came from the 45-64 age groups. The demographic characteristics of respondents to the 2003 survey were similar to those of other contemporary Australian studies [3,24], supporting the suggestion that respondents were broadly representative of Australians with MS. Some of the differences that were found with published studies are described below (see Discussion: limitations of study).…”
Section: Respondentssupporting
confidence: 71%
“…Both the MS and control groups were predominantly women (66.7% and 63.3%, respectively), and did not signifi cantly differ in the number of years of education [ M = 15.0, SD = 3.44 and M = 14.8, SD = 2.57, respectively; t (55) = 0.32, p = .75]. Overall, the characteristics of the MS participants were broadly comparable with those from a recent database sample including 2618 respondents with a diagnosis of MS in New South Wales (see Tribe et al, 2006 ).…”
Section: Emotion Understanding Diffi Culties In Msmentioning
confidence: 60%
“…Pozzilli, Brunetti, Amicosante, Gasperini, Ristori, Palmisano, et al (2002, p.250) interviewed MS patients in Italy to compare, the cost effectiveness of home based care versus hospital care found that "comprehensive planning of home based intervention implemented by an interdisciplinary team and designed specifically for people with multiple sclerosis may provide a cost-effective approach to management and improve the quality of life". However, Tribe, Longley, Fulcher, Faine, Blagus, Pearce, et al (2006) in their study of Multiple Sclerosis patients living in New South Wales, Australia, found that for those living further away from major cities personal support needs were less reliable.…”
Section: Rapidly Degenerative Conditions and The Support They Needmentioning
confidence: 98%
“…Tribe et al (2006) also found that services for rural clients were less reliable. The program is reliant on brokering other service providers to perform in-home services and clients are required to travel to the metropolitan area for out-of-home respite.…”
Section: Accessing Services In Rural Areasmentioning
confidence: 98%
See 1 more Smart Citation